Measurement of absorbed dose to water around an electronic brachytherapy source. Comparison of two dosimetry systems: lithium formate EPR dosimeters and radiochromic EBT2 film. (23rd April 2015) - Adolfsson, Emelie; White, Shane; Landry, Guillaume; Lund, Eva; Gustafsson, Håkan; Verhaegen, Frank; Reniers, Brigitte; Carlsson Tedgren, Åsa; Carlsson, Gudrun Alm
Abstract: Interest in high dose rate (HDR) electronic brachytherapy operating at 50 kV is increasing. For quality assurance it is important to identify dosimetry systems that can measure the absorbed doses in absolute terms which is difficult in this energy region. In this work a comparison is made between two dosimetry systems, EPR lithium formate dosimeters and radiochromic EBT2 film. Both types of dosimeters were irradiated simultaneously in a PMMA phantom using the Axxent EBS. Absorbed dose to water was determined at distances of 10 mm, 30 mm and 50 mm from the EBS. Results were traceable to different primary standards as regards to absorbed dose to water (EPR) and air kerma (EBT2). Monte Carlo simulations were used in absolute terms as a third estimate of absorbed dose to water. Agreement within the estimated expanded ( k = 2) uncertainties (5% (EPR), 7% (EBT2)) was found between the results at 30 mm and 50 mm from the x-ray source. The same result was obtained in 4 repetitions of irradiation, indicating high precision in the measurements with both systems. At all distances, agreement between EPR and Monte Carlo simulations was shown as was also the case for the film measurements at 30mm and 50mm. At 10mm the geometry for the film measurements caused too large uncertainty in measured values depending on the exact position (within sub-mm distances) of the EBS and the 10 mm film results were exculded from comparison. This work has demonstrated good performance of the lithium formate EPR dosimetry system in accordance with earlier experiments at higher photon energies ( 192 Ir HDR brachytherapy). It was also highlighted that there might be issues regarding the energy dependence and intrinsic efficiency of the EBT2 film that need to be considered for measurements using low energy sources.